Pengaruh Green Marketing dan Product Quality Melalui Brand Image Terhadap Purchase Intention Generasi Z - Nicholas Santoso; Joel Faruk Sofyan (MES Bogor, 2026)
Amidst increasing consumer awareness of environmental issues and increasingly fierce competition in the fashion industry regarding Green Marketing in Generation Z. This generation is known as a critical consumer group, digitally literate, and has a high attention to the value of sustainability, Product Quality and brand image. This study aims to analyze the effect of Green Marketing and Product Quality on Purchase Intention with Brand Image as a mediating variable in consumers of Cottonink fashion products from Generation Z. This study uses a quantitative approach with a survey method. The number of samples used was 200 respondents who are consumers of Cottonink fashion products. The sampling technique used a purposive sampling method, while data analysis was carried out using Structural Equation Modeling–Partial Least Squares. The results of the study indicate that Green Marketing and Product Quality have a positive effect on brand image. Product Quality and Brand Image have a positive effect on Purchase Intention while Green Marketing has no significant effect on Purchase Intention. In addition, Brand Image can mediate the effect of Green Marketing and Product Quality on Purchase Intention. These findings indicate that the success of the Green Marketing strategy in increasing Purchase Intention of Generation Z needs to be supported by a strategy to strengthen Brand Image with a sustainability perspective. Besides that, companies also need to continuously maintain and develop Product Quality because it can improve Brand Image and Purchase Intention.